Indigenous trajectories at the university: The right to higher education in Rio de Janeiro - Kelly Russo; Edson Araújo Diniz (Arizona State University, 2020)
This article aims to discuss the access and permanence of indigenous students in higher education, based on a field work conducted with young people of different ethnicities, university students from public and private institutions in the state of Rio de Janeiro. Through a work of historical revision on the right to education of the indigenous populations in the country, the analysis of documents and interviews conducted to students, we verified the need to improve the entry process and the conditions of permanence of these students, executing and making feasible an expansion of public affirmative action policies aimed at the inclusion of indigenous populations in higher education in the state of Rio de Janeiro.